O Mariach i Martach tego świata. Kobieta oczami Orzeszkowej na podstawie powieści "Maria" - Miera, Hanna (2022)
The subject of the article is an analysis of Eliza Orzeszkowa’s views on the situation of women in the second halfof the 19th century and the social roles assigned to them. The epistolary novel Maria, which was juxtaposed withthe dissertation A few words about women, was the main focus of the analysis. In the introduction to the novel,Orzeszkowa referred to Maria as Marta’s sister, whom she follows. In this way she referred to her most famousemancipation novel. Maria, considered by researchers to be one of the writer’s least successful works, gives theimpression of being far from any emancipatory assumptions. However, behind the lofty aspiration of an individualto devote themselves to the idea, there are real problems that many women of that era, including Orzeszkowa herself,had to deal with.
Keywords: 19th century; women’s rights; emancipation; Maria; Marta